Optimizing Gallium Nitride (GaN) Based Inverters for Next-Generation Electric Vehicle Fast-Charging Stations (Aintelia Science Notes, 2024)
Gallium nitride (GaN) high-electron-mobility transistors (HEMTs) are rapidly emerging as the enabling technology for next-generation electric vehicle (EV) fast-charging stations, offering superior switching performance over conventional silicon-based devices. This paper investigates the optimisation of GaN-based two-stage inverter architectures — comprising a totem-pole bridgeless power factor correction (PFC) front-end and an LLC resonant DC-DC stage — for high-power EV fast-charging applications. Key optimisation parameters including switching frequency selection, dead-time minimisation, zero-voltage switching (ZVS) range extension, and thermal management strategies are systematically analysed. The comparative performance of GaN against silicon carbide (SiC) and silicon (Si) devices is evaluated across efficiency, power density, and electromagnetic interference (EMI) dimensions. Results indicate that GaN-based inverters can achieve power conversion efficiencies exceeding 98% at switching frequencies of 100-500 kHz, with passive component volume reductions of 30-60% relative to Si baselines. Implementation challenges including dynamic on-resistance degradation, gate-driver design complexity, and high-frequency EMI compliance are critically examined. The paper concludes with a topology-selection framework and a research roadmap for GaN deployment in 400 V and 800 V EV charging architectures.